Skabelsen af et tredje helle: Badious post- og anti-nietzscheanske læsning af Paulus - Anders Klostergaard Petersen (Religionsvidenskabeligt Tidsskrift, 2017)
The article discusses Badiou’s reading of Paul. Although it would be easy to criticise it on the basis of its overly anachronistic character, I argue that there may be more to it. I present his reading and situate it in the framework of his wider philosophical oeuvre. Core issues are the ideas of anti-philosophy, subjectivity, the event, the fabulous, singularity, universalism, and love. I accentuate Badiou’s use of Paul as exemplary of a post- and anti-Nietzschean philosophical undertaking. Four critical points are raised against Badiou’s use of Paul: (1) a lack of historical appreciation of the type of religion Paul represents. Had Badiou acknowledged the Axial Age character of Paul’s religiosity, he could have strengthened his argument by undergirding it historically; (2) a problematic element of anti-Judaism relating to the juxtaposition of Pharisees with Pétainists; (3) although Paul may be seen to revolt against one particular type of particularism, it is difficult to see how one can possibly surmise that Paul’s worldview and the role he ascribes to Christ-adherents can evade the accusation of exemplifying another form of particularism; (4) throughout Badiou’s reading, there is a lack of lucidity in the use of concepts and in the ductus of the philosophical argument. At points, the argument borders mysticism and religious discourse.